Effects of Ramosetron on Gastrointestinal Transit of Guinea Pig - Park, Yoo Mi (Korean Society of Neurogastroenterology and Motility, 2013)
BACKGROUND/AIMS: A selective 5-hydroxytryptamine (5-HT) type 3 receptor antagonist, ramosetron, inhibits stress-induced abnormal defecation in animals and is currently used as a therapeutic drug for irritable bowel syndrome with diarrhea. The aim of this study is to investigate the effect of ramosetron on altered gastrointestinal (GI) transit. METHODS: Male guinea pigs weighing approximately 300 g were used. The effect of ramosetron was investigated on altered GI transit induced by thyrotropin-releasing hormone (TRH), 5-HT, or mustard oil (MO). GI transit was evaluated by the migration of charcoal mixture from the pylorus to the most distal point, and expressed as a percentage (%) of charcoal migration (cm) of the total length of total small intestine (cm). RESULTS: The average charcoal transit was 51.3 ± 20.1% in the control (vehicle) group, whereas in the ramosetron group charcoal moved 56.6 ± 21.9%, 46.9 ± 9.14% and 8.4 ± 5.6% of the total small intestine at the concentrations of 10, 30 and 100 µg/kg, respectively. GI transit after administration of TRH (100 µg/kg), 5-HT (10 mg/kg) or MO (10 mg/kg) was accelerated compared to vehicle (5-HT, 94.9 ± 9.22%; TRH, 73.4 ± 14.7%; MO, 81.0 ± 13.7%). Ramosetron inhibited GI transit altered by 5-HT, TRH or MO. CONCLUSIONS: Ramosetron modulated GI transit. We suggest that ramosetron may be therapeutically useful for those with accelerated upper GI transit.